Isolation and Identification of Diseases Affecting Dragon Fruit (Hylocereus sp.) in Banyuwangi and Bogor, Indonesia - Retno, Dinda Ambaria; Damayanti, Tri Asmira; Tondok, Efi Toding (HAYATI Journal of Biosciences, 2026)
Dragon fruit (Hylocereus sp.) or pitahaya is a high-value horticultural commodity driven by strong domestic demand. However, national production remains insufficient, leading to continued reliance on imports. One of the main obstacles in dragon fruit cultivation is the emergence of diseases. Currently, information regarding dragon fruit diseases in Indonesia is still limited. This study aims to identify diseases affecting dragon fruit, characterize their symptoms, determine the causative pathogens, and calculate disease incidence. Sampling and disease incidence calculation were conducted in Bogor and Banyuwangi, followed by isolation and identification in the laboratory. Fungal diseases found in dragon fruit plants include anthracnose (Colletotrichum sp.), leaf blight (Fusarium sp.), dragon fruit stem canker (Neoscytalidium dimidiatum), rust disease (Cephaleuros sp.), and white stem disease. The bacterial disease found in dragon fruit plants is rot, which is believed to be caused by Staphylococcus sp. Symptoms of yellowish systemic spots are considered to be caused by a virus (Cactus Virus X). Nematodes identified on dragon fruit roots include Helicotylenchus sp., Heterodera sp., and Rhabditis sp. however, no typical symptoms usually associated with nematode attacks were observed on the host plants. Stem canker is the most prevalent disease, with an incidence ranging from 58.7% to 100%.